2021
DOI: 10.1021/acs.chemrestox.1c00023
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Disrupting Effect of Benzophenone-1 Chlorination Byproducts to the Androgen Receptor: Cell-Based Assays and Gaussian Accelerated Molecular Dynamics Simulations

Abstract: Benzophenone-1 (BP-1), one of the commonly used ultraviolet filters, has caused increasing public concern due to frequently detected residues in environmental and recreational waters. Its susceptibility to residual chlorine and the potential to subsequently trigger endocrine disruption remain unknown. We herein investigated the chlorination of BP-1 in swimming pool water and evaluated the endocrine disruption toward the human androgen receptor (AR). The structures of monochlorinated (P1) and dichlorinated (P2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, the important π stacking is rather unstable between AChE and ( R )-isocarbophos, which is in line with the overall trend of conjugated effects obtained from MD simulation, that is, the conjugated effects of the AChE–( R )-isocarbophos adduct have a markedly weakening trend, whereas it is not observed to be distinctly changed in the AChE–( S )-isocarbophos complex. Besides, for the solvation free energy, we found that the polar solvation contribution (Δ G pol,sol ) played a major role in both neurotoxic reactions, and the energy data were 60.64 and 61.15 kcal mol –1 , respectively, the energy difference was Δ E = −0.51 kcal mol –1 , manifesting that the polar solvation contribution (Δ G pol,sol ) has almost the same influence on the free energy. , Clearly, these energy-scale results clarified the important reasons for the different biological affinities in the stereoselective toxic conjugations, namely, ( R )-isocarbophos has a lower neurotoxic reactivity to AChE compared with ( S )-isocarbophos. In other words, the toxic affinity of ( S )-isocarbophos with AChE is markedly better than that of ( R )-isocarbophos, and as an inhibitor, the strong modes of enantiomeric toxic action means that ( S )-isocarbophos has a more significant inhibitory effect on synaptic AChE, which is dovetailed with the results of SH-SY5Y nerve cell-based assays.…”
Section: Resultsmentioning
confidence: 63%
“…However, the important π stacking is rather unstable between AChE and ( R )-isocarbophos, which is in line with the overall trend of conjugated effects obtained from MD simulation, that is, the conjugated effects of the AChE–( R )-isocarbophos adduct have a markedly weakening trend, whereas it is not observed to be distinctly changed in the AChE–( S )-isocarbophos complex. Besides, for the solvation free energy, we found that the polar solvation contribution (Δ G pol,sol ) played a major role in both neurotoxic reactions, and the energy data were 60.64 and 61.15 kcal mol –1 , respectively, the energy difference was Δ E = −0.51 kcal mol –1 , manifesting that the polar solvation contribution (Δ G pol,sol ) has almost the same influence on the free energy. , Clearly, these energy-scale results clarified the important reasons for the different biological affinities in the stereoselective toxic conjugations, namely, ( R )-isocarbophos has a lower neurotoxic reactivity to AChE compared with ( S )-isocarbophos. In other words, the toxic affinity of ( S )-isocarbophos with AChE is markedly better than that of ( R )-isocarbophos, and as an inhibitor, the strong modes of enantiomeric toxic action means that ( S )-isocarbophos has a more significant inhibitory effect on synaptic AChE, which is dovetailed with the results of SH-SY5Y nerve cell-based assays.…”
Section: Resultsmentioning
confidence: 63%
“…46 Fig. 14 In addition, avonoids and related phenylpropanoids, which accumulate as ultraviolet-absorbing compounds (27) and cause a decrease in the epidermal UV transmittance (TUV), are the main defenses used by plants against potentially harmful solar UV radiation. These compounds are also essential parts of the overall acclimation reaction of plants to shiing solar UV environments.…”
Section: Flavanoid Based Sunscreenmentioning
confidence: 99%
“…5a ). 27 However, the UV filter components in many sunscreen lotions include benzophenone-8 (BP-8) and benzophenone-3 (8, BP-3). In the adipogenesis model using the bone marrow of human mesenchymal stem cells (hBM-MSCs), the long-wave UV A filter avobenzone's obesogenic action was clarified.…”
Section: Benzophenone Based Sunscreenmentioning
confidence: 99%
“…For potential endocrine disrupting effects of DBPs, previous research focused mainly on determining the effects of some DBPs on various kinds of proteins and cell lines from humans and other mammals. For example, the results from in vitro assay documented that DBPs could interfere hormone transporters (i.e., human transthyretin (hTTR) and human serum albumin), activate/inhibit hormone receptors such as human or rat estrogen receptor, human androgen receptor, ,, peroxisome proliferator-activated receptor gamma (PPARγ), , and retinoid X receptor, and inhibit follicle growth and steroidogenesis in mouse ovarian antral follicles . The in vivo study also found that iodoacetic acid (IAA) could disrupt the rat thyroid system and elicit reproductive and developmental toxicity .…”
Section: Introductionmentioning
confidence: 99%